Epidemiological link between wheat allergy and exposure to hydrolyzed wheat protein in facial soap. Issue 10 (16th August 2014) - Fukutomi, Y.; Taniguchi, M.; Nakamura, H.; Akiyama, K.
Abstract Background Recent studies have highlighted the importance of extra‐intestinal routes of sensitization to food‐related allergens as the cause of epidemics of food allergy. Instances of Japanese women developing food allergy to wheat after exposure to hydrolyzed wheat protein (HWP) present in facial soap have been reported. However, the epidemiologic impact of these ingredients as a cause of food allergy has not been well studied. Methods To clarify the epidemiological relationship between food allergy to wheat and contact exposure to HWP, a case–control study of Japanese women aged 20–54 years with self‐reported wheat allergy (WA) (cases, n = 157) and age‐matched control subjects without WA (controls, n = 449) was performed using a large‐scale Web‐based research panel. Subjects answered a Web‐based questionnaire regarding the use of skin and hair care products, as well as other possible risk factors. Results Current use of an HWP‐containing facial soap (Cha no Shizuku; Yuka) was significantly associated with an increased risk of WA (adjusted odds ratio, 2.6; 95% confidence interval, 1.2–5.7; frequencies of current use in cases and controls; 11% and 6%, respectively). Use of Cha no Shizuku was more common in subjects with more recent‐onset WA, implying that this soap may have contributed to the recent epidemic of WA. Conclusions An epidemiological relationship between WA and contact exposure to HWP has been documented. This study implicates a possible role of contact exposure to food‐derived protein hydrolysates as a risk factor for the development of food allergy manifesting itself as anaphylaxis.